Development Of Technology and Study of Solubility Of «Fatifiltrum» Capsules - Nilufar Ravshan kizi, Umaralieva; Firuza Khurshidovna, Maksudova; Sultanovna, Faizullaeva Nodira (Journal of Neonatal Surgery, 2025)
The article presents the results of experimental studies on the development of the optimal composition of «Fatifiltrum» capsules, formulated based on purified and activated natural glauconite. By analyzing the physical and mechanical properties of purified glauconite and applying experimental design methods—multifactorial plans based on 3×3 Latin squares—the optimal composition of the capsule mass was selected. Additionally, the solubility of «Fatifiltrum» capsules was studied.